2009
DOI: 10.1111/j.1948-7134.2009.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diel patterns of biting midges (Ceratopogonidae) and mosquitoes (Culicidae) on the Parris Island Marine Corps Recruit Depot

Abstract: The Marine Corps Recruit Depot on Parris Island, SC, is surrounded by tidal salt marshes, which are breeding habitats for many pestiferous biting flies. Knowledge of biting fly behavior patterns is needed to develop effective pest management strategies in urban areas adjacent to salt marshes. We measured biting midge (Ceratopogonidae) and mosquito (Culicidae) seasonal abundance and diel activity patterns on Parris Island using CO 2 -baited suction traps from November 2001 -November 2004. Of the three biting mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Many vectors of haemosporidian parasites like mosquitoes and midges (but not louse flies) are particularly active during twilight periods [ 51 ]. A potential host might reduce its infection risk by hiding in shelters during peak times of vector activity.…”
Section: Methodsmentioning
confidence: 99%
“…Many vectors of haemosporidian parasites like mosquitoes and midges (but not louse flies) are particularly active during twilight periods [ 51 ]. A potential host might reduce its infection risk by hiding in shelters during peak times of vector activity.…”
Section: Methodsmentioning
confidence: 99%
“…Mammal-feeding Culicoides spp. are serious pests in coastal areas across North America, including on the Marine Corps Recruit Depot Parris Island (MCRDPI), SC (Breidenbaugh et al 2009, Sloyer et al 2019. Culicoides spp.…”
mentioning
confidence: 99%
“…The MCRDPI has served as a model site for studies on pestiferous Culicoides spp. due to seasonally high pest populations coupled with intense outdoor military training and subsequent potential to cause cellulitis from scratching at bites (Haile et al 1984, Breidenbaugh et al 2009). Haile et al (1984) showed that evening aerial spray operations can reduce Culicoides spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations